Simultaneous Network Reconfiguration with Distributed Generation Sizing and Tap Changer Adjustment for Power Loss Reduction Using Imperialist Competitive Algorithm - Koong, Gia Ing; Mokhlis, Hazlie; Jamian, Jasrul Jamani; Illias, Hazlee Azil; Dahalan, Wardiah Mohd; Aman, Muhammad Mohsin (Springer, 2018)
This paper presents a simultaneous network reconfiguration with DG sizing and tap changer adjustment to minimize power loss in a distribution system. Imperialist Competitive Algorithm is used to identify the best set combination of reconfiguration, DG size and tap changer. The performance of the proposed method has been tested on 33 bus distribution system at different load levels and different scenarios of DGs location. The test results indicated an improvement of power loss reduction as compared to existing method. Furthermore, the simultaneous approach is able to produce lowest power loss than any combination of two components simultaneously. At the same time, voltage also maintains within allowable limit.